Factors Influencing The Favorability Of Patients With Renal Transfer (Texas Journal of Medical Science, 2026)
The article comparatively examines the factors affecting survival in patients who underwent kidney transplantation. The research results confirmed the dependence of survival and transplant loss after kidney transplantation on a number of factors. Among them, age, male sex, long-term dialysis, smoking, diabetes mellitus, chronic heart failure, arterial hypertension, and obesity significantly increase the risk. Insufficient immunosuppression, especially the low dose of tacrolimus, had a serious negative impact on the survival of the transplant. These data confirm that the early detection of high-risk patients, individual monitoring, and optimization of immunosuppressive therapy are crucial for increasing transplant survival. The obtained results confirm the need for a comprehensive approach to assessing post-transplant risk, taking into account clinical, immunological, and transplant-related factors, and not a single factor.